Is Urinary Lipoarabinomannan the Result of Renal Tuberculosis? Assessment of the Renal Histology in an Autopsy Cohort of Ugandan HIV-Infected Adults - Cox, Janneke A. (PLoS One, 2015)
OBJECTIVE: The detection of urinary lipoarabinomannan (LAM), a mycobacterial cell wall component, is used to diagnose tuberculosis (TB). How LAM enters the urine is not known. To investigate if urinary LAM-positivity is the result of renal TB infection we correlated the outcomes of urinary LAM-antigen testing to renal histology in an autopsy cohort of hospitalized, Ugandan, HIV-infected adults. METHODS: We performed a complete autopsy, including renal sampling, in HIV-infected adults that died during hospitalization after written informed consent was obtained from the next of kin. Urine was collected postmortem through post-mortem catheterisation or by bladder puncture and tested for LAM with both a lateral flow assay (LFA) and an ELISA assay. Two pathologists assessed the kidney histology. We correlated the LAM-assay results and the histology findings. RESULTS: Of the 13/36 (36%) patients with a positive urinary LAM ELISA and/or LFA, 8/13 (62%) had renal TB. The remaining 5 LAM-positive patients had disseminated TB without renal involvement. Of the 23 LAM-negative patients, 3 had disseminated TB without renal involvement. The remaining LAM-negative patients had no TB infection and died mostly of fungal and bacterial infections. LAM LFA had a sensitivity of 81% and specificity of 100% to diagnose TB at any location, and the LAM ELISA a sensitivity of 63% and a specificity of 100%. 54% (7/13) LAM LFA-positive patients were not on anti-TB treatment at the time of death. CONCLUSION: Renal TB infection explained LAM-positivity in the majority of patients. Patients with disseminated TB without renal involvement can also be diagnosed with LAM. This suggests that other mechanisms that lead to urinary LAM-positivity exist in a minority of patients.